Impact of Green Vegetables and Green Smoothies on Enamel Mineral Composition In Vitro - Willershausen, Ines; Schulte, Daniel; Willershausen, Brita; Azaripour, Adriano (Iranian Journal of Pediatrics, 2019)
Background: Recently, smoothies with a high vegetable content have become very popular, especially among young adults.
CRIS-Team WoS Importer:2019-07-19